Frasa Bahasa Bali Kuna dan Perkembangannya ke Bahasa Bali Modern - Ni Luh Sutjiati Beratha, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
The Balinese language is the language is only known from Balinese inscriptions dated to 882 – 1050 AD, then evolved to Modern Balinese. This article discusses about Old Balinese phrases and their development to Modern Balinese, i.e. by explaining the structure or word order of the phrases. The Old and Modern Balinese phrases will be analysed by applying a theory of structural linguistic typology which is developed by Greenberg, while the analysis of the internal structure of the phrases uses sub-theory of Government and Binding (GB) which developed by Chomsky and his followers, particularly X-bar theory. The claim of this theory is a phrase always has a head from the same category of a phrase as a whole, and this means that the structure of phrases is always endocentric. Formation role of a phrase is projected from lexicon and in this article the analysis will be presented using a tree diagram.It appears that the Old Balinese and Modern Balinese phrases are endocentric, consisted of noun phrases, verb phrases, adjective phrases, and prepositional phrases which their head are nouns, verbs, adjectives, and prepositions. It is interesting to note that in its development (from Old Balinese to Modern Balinese), there are innovations or some changes have taken place from Old Balinese phrases to Modern Balinese phrases. Innovations in word order change consisted of reversal of word order, simplification or reduction, and elaboration. These innovations are internal and regular.
Keywords: Old Balinese language; Modern Balinese language; phrases; word order; word/phrase order change